The spandrel of masonry buildings: experimental tests and numerical analysis. (2019) - Calderoni, Bruno; Cordasco, Emilia Angela; Pacella, Gaetana; Simoniello, Paolo
The interest of the scientific community for the seismic behaviour of existing masonry buildings is continuously increasing in recent years. The authors have analysed the structural behaviour of spandrels in URM buildings by means of several experimental tests performed on specimens in reduced scale. The results of this experimental campaign are reported in this paper and are compared with the results of several experimental tests on full scale masonry spandrels available in literature. The key-data and the set-up of the tests, the criteria adopted for testing and the results obtained are discussed, in order to underline their effectiveness in defining a theoretical interpretation of the actual mechanical behaviour of spandrels in masonry buildings subjected to seismic actions. Then, some of the tests have been simulated by means of FE models. The comparison between experimental and numerical results shows sensible variation depending on the material modelling and the geometrical properties of the panels.